2019
DOI: 10.3390/met10010062
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behaviors and Microstructure Evolution of Iron–Nickel Based Ultra-High Strength Steel by SHPB Testing

Abstract: Iron–nickel based ultra-high strength steel (wt. 18~20% Ni) is characterized by its high strength and low thermal conductivity, and is normally used to make key components by forming and machining processes. The optimization of these processes is based on a deep understanding of the mechanical and dynamic behaviors under high strain, high strain rate, and high temperature. In this paper, the relationship of stress to strain, strain rate, and temperature is systematically investigated by the dynamic compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This was attributed to the increment in density of dislocations, dislocation accumulation, and formation of twinning. The influence of higher strain rate (between 10 3 to 10 5 /s) attains great impact on mechanical behavior and wear resistance properties of high austenitic Mn steel which may be linked to dynamic strain aging and may delay fracture [81,[89][90][91][92][93].…”
Section: Spd Impacts On the Structure And Mechanical Properties Of Steelsmentioning
confidence: 99%
“…This was attributed to the increment in density of dislocations, dislocation accumulation, and formation of twinning. The influence of higher strain rate (between 10 3 to 10 5 /s) attains great impact on mechanical behavior and wear resistance properties of high austenitic Mn steel which may be linked to dynamic strain aging and may delay fracture [81,[89][90][91][92][93].…”
Section: Spd Impacts On the Structure And Mechanical Properties Of Steelsmentioning
confidence: 99%
“…In this study, that effect has been inversely identified, based on literature values on the same material. High strain rate tensile tests [41] and Charpy tests [42] are usually applied towards the identification of stain rate influence on fracture strain, which is typically modelled through the d 4 parameter in the second term of the Johnson Cook damage initiation model (refer to Equation (2)). An average value was considered (d 4 = 0.03), taking into account the range of literature estimation (0.014 > d 4 > 0.05).…”
Section: Compliance With Metal Cutting Conditionsmentioning
confidence: 99%
“…For example, shotcrete anchor supporting material and filling materials could be preserved. Recently, the continuous development of the Split Hopkinson Pressure Bar (SHPB) experimental technique has resulted in its wide application to the study of dynamic mechanical properties [5][6][7] and constitutive equations [8,9] of materials. Li X.B et al [10] developed a dynamic and static loading test system for rocks at medium to high strain rates, and explored the dynamic mechanical properties of rocks under axial static pressure and confining pressure.…”
Section: Introductionmentioning
confidence: 99%